Listening to Reason : Culture, Subjectivity, and Nineteenth-Century Music - Steinberg, Michael P. (Book collections on Project MUSE., 2004)
This pathbreaking work reveals the pivotal role of music--musical works and musical culture--in debates about society, self, and culture that forged European modernity through the "long nineteenth century." Michael Steinberg argues that, from the late 1700s to the early 1900s, music not only reflected but also embodied modern subjectivity as it increasingly engaged and criticized old regimes of power, belief, and representation. His purview ranges from Mozart to Mahler, and from the sacred to the secular, including opera as well as symphonic and solo instrumental music. Defining subjectivity a.